1968
DOI: 10.1002/dev.420010411
|View full text |Cite
|
Sign up to set email alerts
|

Primiparous and multiparous monkey mothers in a mildly stressful social situation: First three months

Abstract: MrrcHei.t., C . , and STEVENS, C. 'I\'. (1969). Priiniparous und Mttltiparous Monkey Mothers in a .hlildly Stressful Social Situation: First Three hJonths. DEVELOPMENTAL PSYCHOBIOLOGY, l(4): [280][281][282][283][284][285][286]. Eight primiparous rhesus monkey mothers were matched with 8 multiparous rhesus monkey mothers with regard to date of delivery and sex of infant. Each niothei-was housed and tested individually with her infant to preclude the compensating effects of peer experience. The test situation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…Mothers in corncribs were significantly more likely (p =.004) to be primiparous (15 of 26, or 57.7%) than were FR mothers (115 of 375, or 30.7%). Compared to multiparous mothers, maternal behavior of primipara is usually characterized as more “anxious” (2628). Moreover, having a primiparous mother means there are no older siblings available for social interaction, and being born into a cage with other primiparous mothers would result in fewer available older peers.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers in corncribs were significantly more likely (p =.004) to be primiparous (15 of 26, or 57.7%) than were FR mothers (115 of 375, or 30.7%). Compared to multiparous mothers, maternal behavior of primipara is usually characterized as more “anxious” (2628). Moreover, having a primiparous mother means there are no older siblings available for social interaction, and being born into a cage with other primiparous mothers would result in fewer available older peers.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is suggestive in two respects. First, several studies have demonstrated that primiparous mothers are behaviorally less competent than multiparous mothers in caring for their infants [Mitchell and Stevens, 1979;Hiraiwa, 1981;Hooley and Simpson, 1981;Fairbanks, in press). Studies on the functional significance of infant caretaking by nonmothers often make an argument for the beneficial effect of experience in infant handling for the caretaker [Gartlan, 1969;Struhsaker, 1971;Lancaster, 1971;Hrdy, 19761.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of studies have demonstrated how variations in mother–infant interactions can influence offspring development at a genetic [reviewed in Meaney, 2001], cognitive [Murray et al, 1996; Olson et al, 1986], physiological [Feldman, 2012] and behavioral level [Mitchell & Stevens, 1968]. For example, pups of high licking/grooming-arched-back nursing (LG-ABN) rat mothers show reduced physiological and behavioral reactivity to stressful situations, and are themselves better mothers than low LG-ABN mothers [Meaney, 2001].…”
Section: Introductionmentioning
confidence: 99%